2004
DOI: 10.2196/jmir.6.4.e40
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Web-Based vs. Non-Web-Based Interventions: A Meta-Analysis of Behavioral Change Outcomes

Abstract: BackgroundA primary focus of self-care interventions for chronic illness is the encouragement of an individual's behavior change necessitating knowledge sharing, education, and understanding of the condition. The use of the Internet to deliver Web-based interventions to patients is increasing rapidly. In a 7-year period (1996 to 2003), there was a 12-fold increase in MEDLINE citations for “Web-based therapies.” The use and effectiveness of Web-based interventions to encourage an individual's change in behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
655
4
16

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 859 publications
(702 citation statements)
references
References 51 publications
27
655
4
16
Order By: Relevance
“…By 2015, 85 % of the EU population are predicted to be internet users (Eurostat 2012) and internet-based interventions are increasing. The degree of behavioural change achievable via internet-based interventions is similar to (Steele et al 2009;Weigold et al 2013), or potentially greater than (Wantland et al 2004), those conducted face-to-face.…”
Section: Introductionmentioning
confidence: 92%
“…By 2015, 85 % of the EU population are predicted to be internet users (Eurostat 2012) and internet-based interventions are increasing. The degree of behavioural change achievable via internet-based interventions is similar to (Steele et al 2009;Weigold et al 2013), or potentially greater than (Wantland et al 2004), those conducted face-to-face.…”
Section: Introductionmentioning
confidence: 92%
“…These practices and the indicators of adherence were as follows: (1) assess one's weight (scored on whether the app provided a means of calculating one's body mass index with an interpretation of what that means), (2) eat a diet rich in fruits and vegetables (scored on whether the app recommended a certain number of daily servings fruits and vegetables or allowed users to track their number of servings each day), (3) perform regular physical activity (scored on whether the app recommended a certain amount of physical each day per week), (4) drink water instead of juice or soda (scored on whether the app recommended a certain number of daily serving of water or allowed users to track their daily servings of water), (5) keep a food diary (scored on whether the app allowed users to track the daily food consumption), (6) maintain calorie balance of in vs. out (scored on whether the app allowed for users to calculate the number of calorie needed in order to meet desired weight loss/maintenance goals given one's activity level), (7) weight loss of 1 to 2 lb a week (scored on whether the app recommended weight loss goals of 1 to 2 lb/week), (8) portion control (scored on whether the app described or illustrated portions sizes or let users look up nutritional information according to portion size), (9) read nutrition labels (scored on whether the app recommended reading labels, described how to properly read labels, or let users look up nutritional information for food items), (10) track your weight (scored on whether the app provided a means to track weight over time), (11) keep a physical activity journal (scored on whether an app provided a means to track daily physical activity), (12) plan meals (scored on whether the app recommended users plan their meals, had a tool for menu planning, or a way to search recipes), and (13) seek social support (scored on whether the app allowed users access to social support components like message boards, chat rooms, email an expert, or a networking component like Twitter).…”
Section: Selecting Apps For Reviewmentioning
confidence: 99%
“…However, research on apps for these and other health promotion purposes has not kept pace with technological innovations, and their efficacy is yet to be determined [11]. While little is known about the efficacy of smartphone apps, a systematic review of the literature on Internet-based approaches concluded that Internet-based approaches are efficacious for improving behavioral outcomes, including in the arena of weight loss [12,13]. Many of the reasons that make Internet approaches promising may apply to smartphone apps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…efficacy, and clinical outcomes [4][5][6][7][8]. While substantial progress has been made, few efficacious EHIs are adopted or sustained in real-world settings beyond the scope of the research project [5].…”
mentioning
confidence: 99%